Australian marsh beetles (Coleoptera: Scirtidae). 2. Pachycyphon, a new genus of presumably terrestrial Australian Scirtidae - Zwick, Peter (Zootaxa, 2013)
The genus Pachycyphon is erected for marsh beetles (Coleoptera: Scirtidae) from tropical rainforests in Queensland, Australia. The following species are included: P. corpulentus sp. n., P. crassus sp. n., P. elegans sp. n., P. funicularis sp. n., P. gravis sp. n., P. monteithi sp. n., P. obesus sp. n., P. pinguis sp. n., P. serratus sp. n., P. turgidus sp. n. (the type species). Females are wingless and have fossorial ovipositors, a terrestrial larval life is therefore hypothesized. Pachycyphon is compared with other genera, especially probable relatives from temperate rainforests in southeasternAustralia.